Predictors of Sleep Habits in Premature Infants: A Cross-Sectional Study - Nooripour, Shamsolah; Ziari, Abbas; Sernizon Guimarães, Nathalia; Hallaj pour, Amir fazel; Zahed, Ghazal; Fatahi, Somaye (Iranian Journal of Child Neurology, 2025)
Objectives: Despite the significant frequency of sleep disorders in premature infants, the specific causes remain unclear. Thus, pediatricians and other caregivers may be able to prevent the onset of sleep disorders in children. Accordingly, the present study aimed to assess the predictors of sleep habits among preschoolers born preterm. Materials & Methods: This cross-sectional, retrospective study included 174 preterm infants from the Semnan clinic in Iran between 2019 and 2020. All children between the ages of four and seven years old who were born before 37 weeks were included. Information on demographic variables and the Children’s Sleep Habits Questionnaire (CSHQ) was collected from the participants. The Research Ethics Committee of the Semnan University of Medical Sciences, Semnan, Iran (IR. SEMUMS.REC.1396.235). Results: The average age of children and mothers were 5.7±0.96 and 32.14 ±2.02 years old, respectively. The probability of familial conflict (OR = 2.73, 95% CI = 0.97-7.71, and P = 0.041), sleepwalking (OR=2.56, 95% CI=1.30-5.06, and p=0.006) and seclusion increased (OR=2.68, 95% CI=0.91-5.13, and P=0.034) in CSHQ 1< to 2 compared with CSHQ >2 in adjusted model History of psychological disorder, sleep drugs use, withdrawn and previously diagnosed sleep disorders, depression, nightmares, and sleeping alone no had significant association with CSHQ score. Conclusion: The study concluded that stress factors, such as family conflicts, behavioral changes like increased seclusion, as well as internal issues like sleepwalking, should be regularly investigated in children referred to clinics for sleep problems. Healthcare professionals need to assess how these symptoms may worsen or impact the effectiveness of treatment.